2020
DOI: 10.37358/rc.20.1.7859
|View full text |Cite
|
Sign up to set email alerts
|

Levels, Sources and Risk Characterization of Organochlorine Pesticides in Beer Samples from Romania

Abstract: The present study describes the analysis of nine organochlorine pesticides (OCPs) occurrence in twenty beer samples commercially marketed and widely consumed in Romania. Levels of these compounds were determined by gas chromatography with electron capture detector (GC-ECD). The results indicated that 20% of the examined samples were contaminated with one OCP residues, while 45% of samples have presented multiple pesticides. Among individual compounds, γ-HCH (Lindane) and p,p, DDE were the main contributors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…OCPs are the most widely encountered contaminants, being described as persistent and bioaccumulating substances prone to long-range transportation [40]. Although severely restricted or banned in many countries, OCPs still appear as contaminants, both in food as well as in the environment [41]. In our study, the major contaminants were mainly found in aquatic plant samples and were represented by HCH isomers, DDTs, and derivatives, as well as endosulfan sulfate.…”
Section: Analysis Of Organochlorine Pesticidesmentioning
confidence: 61%
“…OCPs are the most widely encountered contaminants, being described as persistent and bioaccumulating substances prone to long-range transportation [40]. Although severely restricted or banned in many countries, OCPs still appear as contaminants, both in food as well as in the environment [41]. In our study, the major contaminants were mainly found in aquatic plant samples and were represented by HCH isomers, DDTs, and derivatives, as well as endosulfan sulfate.…”
Section: Analysis Of Organochlorine Pesticidesmentioning
confidence: 61%